The importance of graduate students' needs on supervisory contribution in a Malaysian public University. - Ismail, Affero; Zainal Abiddin, Norhasni (East View Information Services, 2009)
Postgraduate students are those that are building an academic career path after their Higher National Degree or Bachelor Degree. The training and preparation at this level are of vital importance. This culminates into writing of thesis or dissertation. Supervision is an intensive, interpersonally focused one-to-one relationship between the supervisor and the student. In this process, the supervisor is designated to facilitate the student's academic development. The mam objective of this study is to identify the students' needs in terms of supervisory system. Supervisory system in this study will be discussed on research and supervision. Questionnaires were sent to 341 graduate students in a public university by purposive sampling. They were Master or Ph.D students with thesis program. About 184 (53.96%) of them were returned and usable. The majority of respondents found that the supervisory aspects generally very accessible. The study thrust will be to highlight the importance of supervisory contribution to graduate study. Supervisory contributions in this research were categorized into five which are managerial, research, academic, language and interpersonal input. Respondents perceived that managerial input was at the highest priority. It is followed by research input with a mean of 4.26. Academic and Interpersonal Input was rating at the third and fourth rank with mean of 4.22 and 4.21. Language inputs fall at the last rank. The study revealed that postgraduate students have different approaches in what they perceived as an effective supervision. The study also revealed that there certain needs highlighted by graduate students to be practiced. Therefore, balancing these needs is very crucial to the successful supervision of postgraduate research projects. Developing skills towards an effective supervision needs to be tackled in various ways. Effective supervisor is essential to guide postgraduate students during their progress in graduate study.